Advertising: principles and practice - Wells, William; Burnett, John; Moriarty, Sandra (New Jersey: Prentice Hall, 1998)
Contents: part 1: advertising foundations and environment: cap 1. introduction to advertising. 2. advertising and society ethics and regulation. 3. advertising and the mark process. 4. advertising agencies. part 2. advertising background, planning and strategy. part 3. advertising media. part 4. creating advertising. part 5. advertising operations. part 6. miscellaneous advertising
Keywords: Mercadeo; Publicidad